Prevalence and Determinants of Oral Mucosal Lesions among Tobacco Users - Safdar, Shamayem; Qazi, Sakina; Khan, Safana; Shahid, Amira; Naz, Sadia; Anjum, Saba (Journal of Neonatal Surgery, 2025)
Objective: To find out the rate of oral mucosal lesions in tobacco users and to explore key related factors with the onset of oral lesions. Methodology: A cross-sectional study was conducted in 110 habitual tobacco users, who had been in a dental outpatient department. Participants were recruited using a non-probability consecutive sampling technique. The structured questionnaire was used to determine demographic characteristics, nature and duration of tobacco exposure, and frequency of consumption. Statistical analyses were performed to assess associations with a significant level of p values less than 0.05 using statistical techniques such as descriptive statistics and chi-square tests. Results: The mean age of the participants was 42.7 +- 11.5 years, 70.9 percent were males and 47.3 percent of the sample smoked some form of tobacco who were using smokeless tobacco, and 40.9 percent were smokeless tobacco users consuming a smoked type of tobacco. Oral mucosal lesions were common among this group of people (58.2%), with leukoplakia (19.1%) and oral submucous fibrosis (16.4%) being the most widespread. It was found that the occurrence of lesions was substantially elevated depending on the duration of the use (p = 0.004) as well as smokeless tobacco use (p = 0.03). Conclusion: Mucosal lesions of the oral mucosa are of high prevalence among users of tobacco, especially the users who are involved in the prolonged or smokeless consumption of tobacco